Equipment management trial : TAHI summary - Victoria Haines; Mike Patterson; J. Bryce; Graham Nicholls; R. Wood; Andrew Deeming; Catherine Cooper; M. Newborough (2005)
The Equipment Management (EM) trial was one of the practical initiatives conceived and implemented by members of The Application Home Initiative (TAHI) with strong support from the DTI, to demonstrate the feasibility of interoperability between white and brown goods, and other domestic equipment. The trial ran from October 2002 to June 2005, over which period it achieved its core objectives through the deployment in early 2005 of an integrated system in trials in 15 occupied homes. Prior to roll out into the field, the work was underpinned by soak testing, validation, laboratory experiments, case studies, user questionnaires, simulations and other research, conducted in a single demonstration home in Loughborough, as well as in Universities in the East Midlands and Scotland. The trial was conducted against a backdrop of continual commercial change. Despite this difficult operating environment, the trial met its objectives, although not entirely as envisaged initially – a tribute to the determination of the trial’s membership, the strength of its formal governance and management processes, and especially, the financial support of the dti. The equipment on trial featured a central heating/hot water boiler, washing machine, security system, gas alarm and utility meters, all connected to a home gateway, integrated functionally and presented to the users via a single interface. The trial met its principal objective to show that by connecting appliances to each other and to a support system, benefits in remote condition monitoring, maintenance, appliance & home controls optimisation and convenience to the customer & service supplier could be provided. The EM trial identified exciting opportunities for the UK’s domestic white and brown goods manufacturing sector. Despite the relative immaturity of some of the enabling technologies people seem interested in the use of smart home devices to improve their quality of life or just generally make things easier at home in their busy schedules. Whilst the enabling technology behind future smart homes is being developed at a rapid pace, it is the intelligent application and integration of this technology that will make the difference to the home consumer. Just because the technology provider can make a ‘useful’ device it does not necessarily mean that the consumer actually wants to buy the ‘new’ invention. The EM trial has successfully shown where certain technology can be deployed successfully and also identified areas where further work is required.